PERANCANGAN STOK BARANG DENGAN SYSTEM BERBASIS EXCEL - Rangga Wirayuda Kurniawan; Abrori Zaki, Paduloh (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2024)
Initially, Teraza Coffee recorded product inventory using manual recording or silent recording on paper and books. Recording remembers information about the arrival of merchandise from the provider and information about active products as merchandise offered to customers. With a conventional information recording process, Terazza is a coffee located in a busy city center. This coffee offers its customers a variety of coffee drinks and snacks. In running a business, inventory is one of the key success factors. The aim of this research is to analyze Warkop Terazza's inventory management. The survey results show that inventory management has been managed well, but challenges still remain, such as difficulties in estimating customer demand and managing inventory.